KECEPATAN MEMBACA EFEKTIF ARTIKEL ILMIAH POPULER SISWA KELAS VIII SMP NEGERI 5 UKUI KABUPATEN PELALAWAN - Mia Fatma Rosida; Elvrin Septyanti; Zulhafizh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the effective reading speed of non-fiction scientific articles among eighth-grade students at SMP Negeri 5 Ukui using a descriptive quantitative approach. Data were obtained through reading speed tests and comprehension tests using cognitive aspects of reading literacy. Data analysis was performed using the formula reading speed x reading comprehension, then categorizing the KEM level at the junior high school level. The results of the study indicate that the students' KEM is very high, with an average of 124 kpm, and their reading comprehension is categorized as high, with an average of 67. These findings suggest that although students can read quickly, comprehension still needs to be improved through regular practice and strategies that balance both aspects in learning.